SME loan banking in Bangladesh: performance prospect of IDLC Finance Limited on SME - Robin, Md. Zahidul Haque (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.